Managing subthreshold leakage in charge-based analog circuits with low-VTH transistors by analog T- switch (AT-switch) and super cut-off CMOS (SCCMOS). - Ishida, K. (IEEE Journal of solid state circuits)
The analog T-switch (AT-switch) scheme is introduced to suppress subthreshold-leakage problems in charge-based analog circuits such as switched capacitors and sample-and-hold circuits. A 0.5-V sigma-delta modulator is manufactured in a 0.15-μm FD-SOI process with low VTH of 0.1 V using the concept. The scheme is compared with another leakage-suppression scheme based on super cut-off CMOS (SCCMOS) and the conventional circuit which are also fabricated. The sigma-delta modulator based on AT-switch greatly improves 8.1-dB SNDR through reducing nonlinear leakage effects while the modulator based on SCCMOS improves the dynamic range rather than the SNDR by comparing with the conventional sigma-delta modulator.